El Foedus de Gadir del 206 a. C.: Una revisión - López Castro, José Luis (Florentia Iliberritana, 2016)
The paper is a review of the problem of the foedus concluded between Gádir, the phoenician town of South Spain, and Rome in 206 B.C., which have been studied by many scholars from both historical and roman law perspectives. The author suggests a new interpretation of the treaty based on the evidence of litterary sources and on the general context of the Second Punic War in Spain. The foedus would be established with the participation of P. Comelio Scipion.